Aging in Place and the Basic Parameters of Geographical Gerontology in Turkey - Esendemir, Serif (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2016)
The populations of all countries in the world gray as the days go by. Although Turkey has a young population, it is also a rapidly aging country as a result of low birth and death rates and long life. expectancies. The growing aging population has made senior citizens problems more apparent. In particular, the question of whether living spaces are arranged in line with the needs of the elderly people has gained momentum. Similarly, geographical gerontology, a sub discipline of gerontology that studies the relationship between older adults and their living places, has gained greater significance. In this study some reflections on Rowles' theory of insideness (autobiographic, physical, and social components/parameters) will be studied to examine the relationship between elderly people and their living spaces in Turkey. Using the qualitative method, in-depth interviews were carried out with 30 nursing-home managers to understand the autobiographical parameter through their nursing homes, the physical parameter through aging in place (with therapeutic spaces as an alternative), and the social parameter through their perceptions of the retirement community network in Istanbul. As a result, this study sheds some light on the question of whether elderly people, who are seen as prisoners of place, have a say in redesigning their place of residence or developing alternative, multi-provisional residences.
Keywords: Geographical gerontology; Aging; Nursing homes; Social policies; Migration; AGE; Sociology